The Role of Motivation to Promote Personal and Social Responsibility Through PE and Sport: A Comparative Exploratory Investigation of Prospective PE Teachers and Sports Leaders in Hungary and Spain - Istvan Soos; Ian Whyte; Diana Szekeres; Karoly Ozsvath; Attila Szabo; Jonathan Ling; Jose Francisco Jiménez-Parra; Alfonso Valero-Valenzuela (Physical Activity and Health)
Background: Increasingly, young people are exposed to or exhibit socially toxic negative behaviours illustrating a need to influence behaviour positively by developing personal and social responsibility. University students studying sports-related courses are the teachers or sports leaders of the future and, if motivated to do so, can strongly influence young people to acquire personal and social responsibility. This study had three aims. First, identify the academic motivational profiles of university students taking sports-related courses. Second, to define relationships within the students’ motivational profiles, resilience, personal and social responsibility, and their intentions to maintain physically active lifestyle after graduation. Third, to investigate if there were differences between Spanish and Hungarian students, and between male and female students. Method: A cross-sectional, cross-cultural comparative quantitative study was conducted with university students (n = 368) from Spain (n = 109 males, 67%) and Hungary (n = 108 males, 53%) using a demographic questionnaire and six validated questionnaires). Data was analysed by IBM SPSS v. 29.0 statistical software package. Results: Results showed that university students’ academic motivations were influenced both by internal and external reasons; however, autonomous motivation demonstrated a medium correlation with personal responsibility, social responsibility, emotional repair, and resilience. Positive relationships were revealed between personal responsibility and social responsibility, motivation (especially autonomous motivation) and the desire for being physically active. Differences were found by country and by sex. Discussion: We suggest that a hybridised model incorporating Teaching Personal and Social Responsibility and the Sports Education Model is employed with sport and physical education students to optimise potential for transfer of values and behaviours.